RAP1-RAC1 Signaling Has an Important Role in Adhesion and Migration in HNSCC - Liu, M.; Banerjee, R.; Rossa, C. [UNESP]; D’Silva, N. J. (SAGE Publications, 2020)
Cell-cell adhesion is a key mechanism to control tissue integrity and migration. In head and neck squamous cell carcinoma (HNSCC), cell migration facilitates distant metastases and is correlated with poor prognosis. RAP1, a ras-like protein, has an important role in the progression of HNSCC. RAC1 is an integrin-linked, ras-like protein that promotes cell migration. Here we show that loss of cell-cell adhesion is correlated with inactivation of RAP1 confirmed by 2 different biochemical approaches. RAP1 activation is required for cell-matrix adhesion confirmed by adhesion to fibronectin-coated plates with cells that have biochemically activated RAP1. This effect is reversed when RAP1 is inactivated. In addition, RAP1GTP-mediated adhesion is only facilitated through α5β1 integrin complex and is not a function of either α5 or β1 integrin alone. Moreover, the inside-out signaling of RAP1 activation is coordinated with RAC1 activation. These findings show that RAP1 has a prominent role in cell-matrix adhesion via extracellular matrix molecule fibronectin-induced α5β1 integrin and supports a critical role for the RAP1/RAC1 signaling axis in HNSCC cell migration.
Keywords: cal adhesion kinase; extracellular matrix; fibronectin; integrin α5β1; small GTPases; squamous cell carcinoma